Functional imaging in neurosciences - Kamath, Sriganesh; Umamaheswara Rao, G S (Journal of Neuroanaesthesiology and Critical Care, 2015)
Recent advances in functional imaging of the brain have enabled a better understanding of the brain functions in health and disease. Amongst various functional imaging techniques, functional magnetic resonance imaging (fMRI) has been more rigorously employed in both clinical practice and in the research arena. This review will discuss the principles and techniques of fMRI, its role in understanding the pathophysiology of brain injury and finally, its clinical application in diagnosing neurological conditions and prognostication of outcome in patients with neurological disorders.
Keywords: Brain injury; functional magnetic resonance imaging; functional imaging; neurosciences; trauma